2007
DOI: 10.1111/j.1540-8159.2007.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy in a Case of Myotonic Dystrophy (Steinert's Disease) and Dilated Cardiomyopathy

Abstract: Steinert's disease (Dystrophia myotonica type 1) is an autosomal dominant neuromuscular disease characterized by myotonia, muscle weakness, frontal balding, cataracts, cardiac conduction abnormalities, especially long PR interval and wide QRS complex. Although subclinical mild myocardial dysfunction may be detected in this syndrome, overt myocardial dysfunction with heart failure called as "myotonic heart disease" is not frequent. Cardiac resynchronization therapy is an effective treatment modality to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“… 121) In both types of myotonic dystrophy, the myocardium may be affected in the form of dCMP or LVHT. 122) 123) 124) Myocardial involvement may also progress to myocardial fibrosis, thereby manifesting as LGE on cMRI. 125) In a study of 129 MD1 patients, CI was found in 55%.…”
Section: Resultsmentioning
confidence: 99%
“… 121) In both types of myotonic dystrophy, the myocardium may be affected in the form of dCMP or LVHT. 122) 123) 124) Myocardial involvement may also progress to myocardial fibrosis, thereby manifesting as LGE on cMRI. 125) In a study of 129 MD1 patients, CI was found in 55%.…”
Section: Resultsmentioning
confidence: 99%
“…To date, very few studies have reported cardiac resynchronization in DMD and BMD 83,90,217,218 and DM1. [219][220][221] There are no data regarding His bundle or left bundle pacing in patients with NMDs, which are both promising strategies to minimize perioperative risks while potentially preserving the benefits of CRT. Early resynchronization in patients with LBBB or wide QRS complex inferring His-Purkinje disease may eliminate the detrimental effects of desynchronized ventricular conduction and further deterioration of LVEF.…”
Section: Recommendation-specific Supportive Textmentioning
confidence: 99%
“…Nonetheless, the decision on cardiac synchronization needs to take into account the presence of comorbidities and their effect on patient prognosis, particularly with regards on pacing only versus defibrillator implantation [43]. Isolated case reports have demonstrated benefits from cardiac resynchronization suggesting this could be a viable option in DM1 patients fulfilling criteria on an individual basis [65][66][67].…”
Section: Ventricular Arrhythmia and Sudden Cardiac Deathmentioning
confidence: 99%